The spatial side of somatoparaphrenia: a case study. Issue 2 (3rd March 2016) - Salvato, Gerardo; Gandola, Martina; Veronelli, Laura; Agostoni, Elio Clemente; Sberna, Maurizio; Corbo, Massimo; Bottini, Gabriella
Abstract: The perception of the bodily self in space is a composite cognitive function requiring a dynamic integrated brain mechanism. Somatoparaphrenia (SP), a delusional belief concerning the experienced disownership for the contralesional paralyzed arm, represents the disruption of such mechanism. In two experiments, we have investigated the alteration of limb disownership after spatial manipulations in a right-brain-damaged patient affected by chronic SP. In experiment 1 the patient's spatial attention was switched between the left and right sides of space. SP signs worsened when the patient was interviewed from the left compared to the right bedside. In the second experiment we showed the first systematic transient remission of SP using left caloric vestibular stimulation (CVS), a physiologic manipulation mainly acting on the spatial frame of reference. Taken together, these results shed further light on the spatial nuance of SP and on the importance of vestibular signals for the generation of a coherent body representation. Furthermore, our case study demonstrated the possibility of eliciting more severe SP signs if the patient is interviewed from the left bedside. Additionally, CVS applications may have an important impact on the rehabilitation of these symptoms.